2016
DOI: 10.1097/cej.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol and the incidence of bladder cancer

Abstract: Our aim is to investigate the risk association between allopurinol use and cancer incidence among gout patients using clinical evidence. Newly diagnosed male patients with gout, 20 years or older, were included after excluding those who had a diagnosis of type 2 diabetes, and were followed up for 12 years in a retrospective cohort study of one million outpatients of a national database. The gout patients were matched to male controls by age and first diagnosis date of gout disease. We then estimated the risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, we extracted these data one by one to analyze the pooled effect values of all tumors and single tumors. All included studies, except for one retrospective cohort study (Chen et al, ), were of prospective cohort designs. All subjects with a long‐term follow‐up were randomly selected from the general population or health surveys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we extracted these data one by one to analyze the pooled effect values of all tumors and single tumors. All included studies, except for one retrospective cohort study (Chen et al, ), were of prospective cohort designs. All subjects with a long‐term follow‐up were randomly selected from the general population or health surveys.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have found that hyperuricemia or gout was associated with higher cancer incidence and mortality (Boffetta, Nordenvall, Nyrén, & Ye, ; Chen, Hsieh, Liao, Chan, & Chang, ; Deng et al, ; Juraschek, Tunstall‐Pedoe, & Woodward, ; Kobylecki, Afzal, & Nordestgaard, ; Kolonel, Yoshizawa, Nomura, & Stemmermann, ; Kuo et al, ; Strasak et al, , ; Strasak et al, ; Taghizadeh, Vonk, & Boezen, ; Wandell, Carlsson, & Ljunggren, ; Yang et al, ; Yiu et al, ). However, at least two studies found no associations between cancer and hyperuricemia or gout (Hiatt & Fireman, ; Wu et al, ), and even one study suggested that the lower SUA levels may lead to a higher incidence of lung cancer (Horsfall, Nazareth, & Petersen, ).…”
Section: Introductionmentioning
confidence: 99%
“… 8 In support of this hypothesis, a recent retrospective cohort study found that use of allopurinol, an XDH/XOR inhibitor, for >3 months may significantly increase the incidence of both bladder cancer and all other cancers. 48 Moreover, XDH inhibition by allopurinol may help cancer cells to escape immune surveillance. 49 Although recent publications indicated that advanced cancer patients will benefit from XDH inhibition, 50 , 51 long-term follow-up of patients receiving XDH inhibitors treatment may be necessary to prevent detrimental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically bladder cancer has been shown to be associated with long-term allopurinol use [63]. Erectile dysfunction has also been reported to be more common in patients with gout [64], whereas its relationship with ULT, and specifically to xanthine-oxidase inhibitors, has not been yet studied.…”
Section: Other Conditions Associated With Goutmentioning
confidence: 98%